Characterization and Extraction of Metals from Sea Floor Manganese Nodules - D. W. Fuerstenau; A. P. Herring; M. Hoover (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1974)
The dissolution of nickel, copper, and cobalt from five different samples of well-characterized deep sea manganese nodules was measured as a function of temperature, pH, leaching time, and particle size. Nickel, copper, and cobalt extraction each respond to these variables in a different manner. The results of this investigation indicate that copper and nickel can be selectively dissolved from iron and manganese at moderately low pH, provided the reaction is given sufficient time. A high dissolution of cobalt with dilute sulfuric acid can only be achieved from nodules that have a low iron content (<5%). The most probable rate-controlling step for copper and cobalt dissolution is diffusion through the pores of the nodules, and for nickel dissolution chemical reaction appears to be rate-controlling.